Health Promotion to Individuals with Type II Diabetes Mellitus in the Family Health Strategy (Research, Society and Development, 2022)
This study sought to know the health promotion actions developed by nurses of the Family Health Strategy (FHS) in relation to people with type 2 diabetes. Exploratory research was conducted with a qualitative approach, the study was developed in the municipality of Jardim, located in the Cariri region, south of Ceará, the participants were professional nurses of the Family Health Strategy teams who met the inclusion criteria, the material was collected from semi-structured interviews, and organized according to the analysis proposed in this work. It was found that the participants of the study have a restricted view about the theme addressed, always associating health promotion to the concept of disease prevention, not being mentioned by them to the promotion associated with the empowerment of the individual. It was also evidenced the lack of involvement of family members in the health promotion actions developed. Given the above, it is necessary to implement the Permanent Education Policy in the municipality that implies the reorganization of the work process and provokes in professionals’ reflections about their practice formulating strategies that will positively impact the quality of life of diabetic people.